Analisis Kualitas Pengelolaan Mutu Pelayanan Pendaftaran Pasien di Instalasi Rawat Inap Rumah Sakit Santa Elisabeth Medan - Jetslin Simbolon; Selviani Damayanti Sipayung (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Inpatient services are non-structural service units that provide facilities and organize individual health service activities which include observation, diagnosis, treatment, nursing and medical rehabilitation. Inpatient registration (TPPRI) is the responsible part of the data and information of patients to be hospitalized. Hospitalization is the maintenance of hospital health where the patient stays for at least one day based on referrals from the implementation of other health services. This study aims to find out how the flow of processing the quality of patient registration services at the Inpatient Installation at Santa Elisabeth Hospital Medan. This study aims to find out how the flow of processing the quality of patient registration services at the Inpatient Installation at Santa Elisabeth Hospital Medan. This study is a qualitative descriptive study using purposive sampling, and collected 17 informants, namely 10 inpatients, 3 medical record services, 4 inpatient registration officer service staff at Santa Elisabeth Hospital Medan. Inpatient installation is one of the clinical services that serves patients who have to be treated for one day or more. The assessment of the success rate of services in health services is usually seen from various aspects, namely the level of utilization of facilities, quality and level of service efficiency. Some standard indicators related to health services that are monitored include bed utilization (Bed Occupancy Rate / BOR), average length of stay (LOS), average bed turn over (BTO), and percentage of discharged patients who died ≥ 48 hours of treatment (Net Death Rate/ NDR).